Isolation of Pigeonpox Virus from Severe Infection of Pigeons in Diyala province: Virological and Histopathological Study: Karim S. Al-Ajeeli1, Amer K. Al-azawy2 and Ramzi Al-Ajeeli3 - Al-Ajeeli, Karim S. (The Iraqi Journal of Veterinary Medicine, 2015)
Pigeonpox virus was isolated from severe cases of avipoxvirus infection affecting 64 pigeons in Ba’aquba of Diyala governarate. The virus grew well on chorioallantoic membrane of chick embryos of 11-12 days old, and produced typical pock lesions. Histopathological sections of infected tissue samples revealed typical pox lesions. The virus was identified as Pigeonpox virus using of specific hyper immune serum and indirect immuno-flourescent and indirect immuno-peroxidase tests. The virus agglutinated RBCs of pigeon, fowl, turkey and duck. Experimental infection in pigeons produced moderate infection as compared to the diseased birds, while in chicken the virus produced mild infection.